Analysis of Parent Stress Levels Toward Children in the Online Learning Process During New Normal - Saifuddin Saifuddin; Hasanah Hasanah; Iqbal Iqbal; Silvi Puspa Widya Lubis; Khairatul Ulya (STAI Hubbulwathan Duri, 2023)
The purpose of this study was to analyze the level of stress faced by parents in the online learning process during the new normal era. The research method used was descriptive qualitative, with a case study approach. The research subjects were parents who have early childhood and elementary school, with a total of 10 mothers. The data collection techniques used were observation and interview data analysis, reduction strategies, data display, data interpretation, and data verification. The study findings indicate that parents face various challenges when it comes to online learning at home during the current era of the new normal. These challenges contribute to heightened levels of stress in relation to their children's education. One such challenge is the lack of comprehension among parents regarding the lessons and learning materials provided by the school. Parents often exhibit impatience when assisting their children, and time constraints further exacerbate the situation. Furthermore, parents struggle to motivate their children to engage enthusiastically in learning. Lastly, parents also lack proficiency in utilising electronic devices such as cell phones and laptops.